Postmortem Demonstration of the Source of Pulmonary Thromboembolism: The Importance of the Autopsy - Gina Elhammady; Andrew T. Schubeck; Vicky El-Najjar; Morton J. Robinson (Case Reports in Vascular Medicine)
Periprostatic or paravaginal venous thromboses are rarely considered clinically as sites of clot origin in patients with pulmonary thromboembolism. The majority of emboli have been demonstrated to originate in the veins of the legs. This report raises awareness of pelvic vein thrombosis as a potential source of pulmonary embolism that is rarely considered or detected clinically, and which usually requires postmortem examination for recognition. It also reviews the possible routes emboli may take to reach the lungs.